Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan di Restoran Bebek Garing Tengah Sawah - Ramadhan, Rexa Priyatna W; Waryono, Waryono; Harmawan, Violintikha (Departemen Pariwisata Universitas Negeri Padang, 2024)
The initial implementation of this research was based on observations and supported by comments on Google review. From the results of observations and Google reviews, problems were found regarding service quality and customer satisfaction at the Bebek Garing Tengah Sawah Restaurant. The purpose of this research is to determine the influenced of service quality on customer satisfaction at Bebek Garing Tengah Sawah Restaurant. This research is a quantitative descriptive using a causal associative method. The population of the study were all customers who visited the Bebek Garing Tengah Sawah Restaurant. The sample in this study amounted to 248 people taken through a purposive sampling technique. Collecting data information in this study used a questionnaire with a Likert scale of 4 scores which were tested for validity and reliability. Testing the analysis prerequisites with the normality and homogeneity tests of the data. The data is then tested for the hypothesis with a simple linear regression test and test the coefficient of determination. Based on the results of the study, it was found that the positive influence of service quality on customer satisfaction, service quality had an effect of 20.7% on customer satisfaction and the other 79.3% was an influence caused by variables that were not in this study.